AIRPORT PRESENCE AS PRODUCT DIFFERENTIATION - Berry, Steven (American Economic Review, 1990)
There is now widespread recognition that an airline's operation at a given airport greatly affects its competitive position on routes flown out of that airport (see M. Levine, 1987; S. Borenstein, 1989; S. Morrison and C. Winston, 1989; and myself, 1989, among many others.) Airlines typically defend any competitive advantage as stemming from the lower costs and better service that are said to be generated by hub-and-spoke route systems. Airline critics typically respond that airlines gain by dominating individual airports. Both views are at least plausible. Huband-spoke transportation networks reduce the number of round-trips necessary to carry a given number of passengers on a given set of itineraries, while increasing the number of passenger miles flown. If there are sufficient economies of scale in plane size, then the advantages of hubbing can overcome the disadvantage in passenger miles, resulting in lower total costs. By pooling passengers with different ultimate destinations, a hubbed system can also offer more frequent flights than would be economically feasible under a nonstop system. It also appears, however, that airlines gain other advantages from a large presence at an airport. Incumbent airlines are the major source of financing for many airports and therefore gain a large degree of bureaucratic control over airport operations. This control may enable them to block the entry or expansion of rivals. Airlines with a large presence in a given city also gain advantages from frequent flyer plans and nonlinear travel agent commission schedules (see, again, Levine and others). If the bureaucratic and marketing advantages of airport presence are sufficient to prevent most attempts at entry, then incumbents may gain the ability to exercise traditional market power by restricting output and driving up prices. This paper argues that both simple costreducing and naive stories are inappropriate for the airline industry. I present a model in which consumers are willing to pay a premium for the services of the dominant airline; this premium may be related to a number of factors, including flight frequency, frequent flier miles, and travel agent commission overrides. This model has the advantage of treating oligopoly product differentiation in an explicit way, of treating price as an endogenous variable, and of allowing for airport presence to affect both costs and demand.